Are eco-labels able to go beyond signaling environmental benefits? using eco-labels to communicate the economic value of sustainability in food products - Langaro, D.; Loureiro, S. M. C.; Brântuas, M. (Journal of Strategic Marketing, 2026)
Previous research suggests that the limited mainstream adoption of sustainable consumption is mainly due to consumers’ struggle to perceive compelling economic value in sustainable products, which are often associated with fewer benefits and higher prices. While eco-labels are frequently present in sustainable offerings as a signal of environmental practices, their potential to influence consumers’ perceptions of economic value remains overlooked. Supported by Signaling Theory, the present research investigates whether eco-labels can generate positive perceptions regarding the functional and symbolic benefits of the product itself and, subsequently, impact purchase behavior. Two quantitative studies (Study 1: n = 195; Study 2: n = 392) were implemented. The findings reveal that the impact of eco-labels on purchase is solely influenced by the mediating effects of perceived symbolic benefits, rather than functional benefits. Consumers’ moral convictions regarding sustainable consumption, along with their familiarity and understanding of eco-labels, play a significant role in shaping their behavior. Further implications are drawn.